Interspecies recombination in NSP3 gene in the first porcine rotavirus H in Russia identified using nanopore-based metagenomic sequencing - Krasnikov, Nikita; Yuzhakov, Anton (Frontiers in Veterinary Science, 2023)
During the last decade, porcine rotavirus H was detected in the USA, Asian regions, South Africa, Brazil, and a couple of European countries. In the presented study, the virus was identified in piglets on a farrow-to-finish farm in Russia during metagenomic surveillance. Currently, it is the first identification of this species in the country. As a diagnostic method, nanopore-based metagenomic sequencing was applied. The obtained nanopore reads allowed for the assembly of 10 genome segments out of 11. The phylogenetic analysis revealed the virus belonged to the porcine cluster and had GX-P3-I3-R3-C3-M8-A7-N1-T5-E3-H3 genome constellation. Moreover, three potential new genotype groups for VP3, NSP1, and NSP3 genes were determined. Additionally, a recombination between RVH and RVC in the NSP3 gene was detected. The study provides significant information about a novel RVH strain.